The effect of overweight on the luteinizing hormone level after gonadorelin stimulation test in girls with idiopathic central precocious puberty - Hyun Young Lee; Yoon-Ji Lee; Moon-Bae Ahn; Won-Kyoung Cho; Byung-Kyu Suh (Korean Society of Pediatric Endocrinology, 2018)
Purpose We investigated the effect of overweight on luteinizing hormone (LH) levels after a gonadorelin stimulation test in Korean girls with idiopathic central precocious puberty (CPP). Methods Medical records of 234 girls diagnosed with idiopathic CPP were reviewed retrospectively. CPP was diagnosed when the peak LH levels after gonadorelin stimulation was >5.0 U/L. The enrolled girls had a peak LH level >5.0 U/L after a gonadorelin stimulation test. Selected girls were classified as normoweight (body mass index [BMI] below the 85th percentile with respect to age) and overweight (BMI greater than the 85th percentile with respect to age). Results The peak LH (8.95±2.85 U/L vs. 11.97±8.42 U/L, P<0.01) and peak follicle-stimulating hormone (9.60±2.91 U/L vs. 11.17±7.77 U/L, P=0.04) after gonadorelin stimulation were lower in overweight girls with idiopathic CPP than in normoweight girls with idiopathic CPP. Being overweight was negatively associated with peak LH levels after gonadorelin stimulation test (odds ratio, 0.89; 95 % confidence interval, 0.81-0.98, P=0.02). Conclusions In girls with idiopathic CPP, being overweight led to a lower LH peak after gonadorelin stimulation. Further research is needed to better understand the role of overweight on gonadotropin secretion in precocious puberty.